Gender Differences? Internet Use and Parent–Child Communication About Sex Toward Sexual Attitudes Among Early Adolescents in Taiwan. Issue 2 (June 2015) - Tseng, Ying-Hua; Weng, Chia-Sui; Kuo, Shih-Hsien; Chou, Fan-Hao; Yang, Yi-Hsin; Chiang, Li-Chi
ABSTRACT Background: With the progress of information technology, early adolescents are able to access sex-related information through the Internet easily. This information has been shown to have a significant influence on the sexual health of this population. In addition, parent–child communications about sex affect the sexual health of adolescents. Few empirical studies have focused on early adolescents and gender differences. Purpose: This study explores gender differences between early adolescents in terms of the use of the Internet to obtain sex-related information, parent–child communication, and sex-related knowledge and attitudes. Methods: This cross-sectional and comparative study uses an analysis of covariance and a hierarchical regression for data analysis. The researchers recruited 457 sixth-grade boys (n = 204) and girls (n = 253) in southern Taiwan as participants and used a structured questionnaire to collect data. Results: Participants exhibited significant differences in terms of Internet usage behavior, parent–child communications about sex, and sex-related knowledge and sexual attitudes. The male participants spent more time on "recreation and entertainment" activities on the Internet, whereas their female peers spent significantly more time searching for information. Regarding parent–child communications about sex, girls had better mother–child communications than boys. In addition, no gender-based difference was found for father–child communications about sex. The knowledge of physical changes occurring during puberty and of menstrual healthcare among female participants was superior to their male counterparts. Girls had a more informed sexual attitude, particularly with regard to issues of gender roles, relationships with the opposite gender, and the social aspects of sex. Sex-related knowledge and parent–child communication about sex were the two major predictors of sexual attitudes for boys and girls, respectively. Conclusions: To develop healthy sexual attitudes among early adolescents, nursing professionals, families, and schools should enhance sex-related knowledge and parent–child communications, especially with boys. Early adolescence is a key time to provide sex education and Internet-safety education to both boys and girls to improve their sexual health. This study may serve as a reference for families, schools, researchers, and policymakers for promoting the sexual health of early adolescents.